Evolution of REFe2 (RE = rare earth) phase in Nd-Ce-Fe-B magnets and resultant Ce segregation. (September 2019) - Jin, Jiaying; Zhang, Zhiheng; Zhao, Lizhong; Peng, Baixing; Liu, Yongsheng; Greneche, Jean-Marc; Yan, Mi
Abstract: REFe2 (RE = rare earth) phase has been considered to form spontaneously in Nd-Ce-Fe-B cast strips and inherit into sintered magnets. However, here we report that REFe2 phase, which is absent in starting strip, occurs in as-sintered magnet with an identical composition of 25 wt% Ce. More interestingly, the formation of REFe2 induces apparent Ce-enriched shell surrounding RE2 Fe14 B grain, which is further exacerbated in annealed magnet containing a higher fraction of REFe2 phase. Influences of increasing REFe2 fraction on magnetic performance are revealed. Above findings on REFe2 phase evolution and resultant Ce segregation may shed lights on fabricating high-performance Nd-Ce-Fe-B. Graphical abstract: Here we report two novel findings in the Nd-Ce-Fe-B system, (i) REFe2 phase occurs after sintering and annealing, which is however absent in the starting cast strip with the same Ce substitution of 25 wt.%, as evidenced by the Rietveld refinement result (a) and SAED patterns along three different zone axes of REFe2 phase (b); (ii) Ce segregates at the surface of 2:14:1 main phase grain upon forming additional REFe2 in the as-sintered magnet (c), which is further exacerbated in the annealed one containing higher REFe2 fraction (d).Unlabelled Image